Investigating How Quantum Cryptographic Techniques Can Enhance the Security of Blockchain-Based Artificial Intelligence (AI) Models - Akther, Afroja; Sultana, Tanzina; Arobee, Ayesha; Badhon, Md Bahauddin; Akter, Farhad; Eashrak, Nafiz (Journal of Knowledge Management Practice, 2025)
The integration of blockchain and artificial intelligence (AI) has revolutionized secure, transparent, and decentralized applications. However, the security of blockchain-based AI models remains reliant on classical cryptographic techniques, such as RSA and ECC, which are increasingly vulnerable to emerging quantum computing threats. This study investigates how quantum cryptographic techniques can enhance the security and resilience of blockchain-based AI applications. Specifically, it explores the role of Quantum Key Distribution (QKD) in securing key exchanges, post-quantum cryptographic (PQC) algorithms in fortifying data encryption, and quantum hashing techniques in protecting blockchain consensus mechanisms. The research evaluates the feasibility, implementation challenges, and performance implications of quantum-enhanced security frameworks for AI-driven blockchain networks. By addressing these concerns, this study establishes a foundation for developing quantum-secured blockchain infrastructures that safeguard AI transactions against future quantum threats while ensuring trust, transparency, and scalability in decentralized applications.